Development of a scale to measure successful aging in late middle-aged women - Lee, Do-Young; Noh, Gie-Ok (Edelweiss Applied Science and Technology, 2024)
This study was conducted in two stages, the tool development stage and the tool verification stage, and was based on DeVellis' tool development guidelines. A total of 18 questions were confirmed as a result of developing a successful aging measurement tool for middle-aged women and verifying the validity. It consisted of a total of 5 factors, and in consideration of the characteristics of the items included in each factor, factor 1 was named 'inconvenience of aging', factor 2 was named 'inconvenience of female hormone deficiency', factor 3 was named 'family success', factor 4 was named 'appearance due to aging', and factor 5 was named 'aging and lifestyle change'. It is measured on a 5-point Likert scale, and the score is 18 points to 90 points, which means that the higher the score, the higher the successful aging. The tool developed in this study will be used to measure successful aging status tailored to middle-aged women.